Essential oil composition of sixteen elite cultivars of Mentha from western Himalayan region, India - Rajendra C. Padalia (Maejo International Journal of Science and Technology, 2013)
The hydrodistilled essential oils of 16 cultivars of Mentha, viz. M. arvensis L., M. spicata L. and M. citrata Ehrh., were analysed and compared by gas chromatography and gas chromatography-mass spectrometry. Fifty-seven constituents representing 92.8-99.8% of the total essential oil composition were identified. Monoterpenoids (88.1-98.6%) are the major constituents of the essential oils. The major constituents of the oils in 9 cultivars of M. arvensis are menthol (73.7-85.8%), menthone (1.5-11.0%), menthyl acetate (0.5-5.3%), isomenthone (2.1-3.9%), limonene (1.2-3.3%) and neomenthol (1.9-2.5%). Carvone (51.3-65.1%), limonene (15.1-25.2%), -pinene (1.3-3.2%) and 1,8-cineole (≤0.1-3.6%) are the major constituents in 5 cultivars of M. spicata, while in one cultivar (Ganga) of M. spicata the major constituents are piperitenone oxide (76.7%), α-terpineol (4.9%) and limonene (4.7%). Linalool (59.7%), linalyl acetate (18.4%), nerol (2.0%), trans-p-menth-1-en-2-ol (1.8%), a-terpineol (1.5%) and limonene (1.1%) are the major constituents of M. citrata.